Untargeted and Targeted Metabolomics Reveal the Active Peptide of Eupolyphaga sinensis Walker against Hyperlipidemia by Modulating Imbalance in Amino Acid Metabolism - Yanan Li; Pingping Dong; Long Dai; Shaoping Wang (Molecules, 2023)
The active peptide (APE) of Eupolyphaga sinensis Walker, which is prepared by bioenzymatic digestion, has significant antihyperlipidemic effects in vivo, but its mechanism of action on hyperlipidemia is not clear. Recent studies on amino acid metabolism suggested a possible link between it and hyperlipidemia. In this study, we first characterized the composition of APE using various methods. Then, the therapeutic effects of APE on hyperlipidemic rats were evaluated, including lipid levels, the inflammatory response, and oxidative stress. Finally, the metabolism-regulating mechanisms of APE on hyperlipidemic rats were analyzed using untargeted and targeted metabolomic approaches. The results showed that APE significantly reduced the accumulation of fat, oxidative stress levels, and serum pro-inflammatory cytokine levels. Untargeted metabolomic analysis showed that the mechanism of the hypolipidemic effect of APE was mainly related to tryptophan metabolism, phenylalanine metabolism, arginine biosynthesis, and purine metabolism. Amino-acid-targeted metabolomic analysis showed that significant differences in the levels of eight amino acids occurred after APE treatment. Among them, the expression of tryptophan, alanine, glutamate, threonine, valine, and phenylalanine was upregulated, and that of arginine and proline was downregulated in APE-treated rats. In addition, APE significantly downregulated the mRNA expression of SREBP-1, SREBP-2, and HMGCR. Taking these points together, we hypothesize that APE ameliorates hyperlipidemia by modulating amino acid metabolism in the metabolome of the serum and feces, mediating the SREBP/HMGCR signaling pathway, and reducing oxidative stress and inflammation levels.